Peranan penggunaan model pembelajaran e-learning dalam meningkatkan kualitas pembelajaran - Kumara, Fernanda Rangga; Dewangga, M. Tegar Satria (Academy of Education Journal, 2024)
The rapid development of technology and information has influenced various aspects of life including in the field of education, therefore, educational institutions must be able to anticipate these developments by continuously striving for a program that is in accordance with the needs of students. then in the application it is necessary to make educational innovations, one of the educational innovations by implementing e-learning, e-learning is a new way in the teaching and learning process that uses electronic media, especially the internet as a learning system. The expectation of the e-learning system in the future is that the use of e-learning becomes more effective along with the development of technology and learning methods used. Elearning system development is also expected to not only take into account financial and profitability issues, but also pay attention to the psychological side of students and be able to accommodate the various personalities and ways of learning of each participant.